Effect of Candida albicans’ supernatant on biofilm formation and virulence factors of Pseudomonas aeruginosa through las/rhl System - Ke Zhang; Yingying Huang; Yuting Jiang; Tangjuan Liu; Jinliang Kong; Shuangqi Cai; Zhongwei Wen; Yiqiang Chen (BMC Microbiology)
Abstract Pseudomonas aeruginosa (P. aeruginosa) and Candida albicans (C. albicans) are opportunistic pathogens whose mixed infections can exacerbate microbial dissemination and drug resistance, contributing to high mortality and morbidity rates among infected individuals. Few studies have explored the impact of C. albicans supernatant on P. aeruginosa, and the underlying mechanisms of such mixed infections remain unclear. In this study, we investigated the effects of C. albicans supernatant on biofilm formation and virulence factor activity in wild-type P. aeruginosa PAO1 and its quorum sensing-deficient mutants, ΔlasIrhlI and ΔlasRrhlR. Our results demonstrated that the biofilm formation capability and virulence were significantly higher in the PAO1 group compared to the ΔlasIrhlI and ΔlasRrhlR groups. Furthermore, exposure to C. albicans supernatant significantly enhanced both the biofilm formation and virulence of PAO1, whereas no significant changes were observed in the ΔlasIrhlI and ΔlasRrhlR mutants relative to their respective controls. These findings suggest that C. albicans supernatant may modulate P. aeruginosa biofilm formation and virulence via the las/rhl quorum sensing system.